Comparison of low-dose maximal-intent versus controlled-tempo resistance training on quality-of-life, functional capacity, and strength in untrained healthy adults: a comparative effectiveness study - Liam T. Pearson; Kai T. Fox; Ashleigh Keenan; David G. Behm; Sam Stuart; Stuart Goodall; Gill Barry (BMC, 2024)
Abstract Lack of physical activity is a global issue for adults that can lead to sedentary behaviour and a higher prevalence of health complications and chronic diseases, resulting in reduced quality-of-life (QoL) and functional capacity (FC). A potential strategy to mitigate this inactivity is low-dose resistance training (RT); however, physiological, and psychological responses are limited in evidence. Twenty untrained participants aged 30-60 years old (mean ± SD age 42 ± 7 years, mass 77 ± 13 kg, stature 166 ± 8 cm; 18 females and two males) were recruited and randomly assigned to maximal velocity-intent (MI, n = 10) or controlled-tempo (CT, n = 10) RT according to CONsolidated Standards of Reporting Trials (CONSORT) guidelines. Participants attended one training session per week for 6 weeks, consisting of five sets of five repetitions at 60% of one-repetition maximum (1RM) leg press. The interventions differed only during the concentric phase, with MI group pushing with maximal intent, and CT group pushing in a time-controlled manner (3 s). Outcome measures assessed pre- and post-RT included body mass, body mass index (BMI), strength-to-mass ratio, bipedal balance, 6-minute walk test (6MWT), 30-second sit-to-stand (30s-STS), timed up and go (TUG), and leg press 1RM. Time effects were observed for all demographics and FC-related outcomes, such as identical reductions in mass and BMI (− 2%), improvements in strength-to-mass ratio (25%) leg press 1RM (22%), 6MWT (3%), and 30s-STS (14%), as well as a 9% improvement in both TUG-clockwise and anticlockwise. Results show low-dose once-weekly RT is effective in improving QoL, FC, and strength in untrained healthy adults, regardless of modality. Positive responses from participants suggest an increased likelihood of consistent participation for low-dose once-weekly RT over more intense modalities. Retrospective ClinicalTrials.gov ID (TRN): NCT06107855, 24/10/2023.